Effect of using different diluted concentrations of pineapple juice extract to remove adhesive substance from common carp(Cyprinus carpio L.) eggs. - Al-humairi, Kadhim Obaid Mutar (Journal of Kerbala for Agricultural Sciences, 2016)
Pineapple juice extract are used at a diluted concentrations ( 0.0001,0.0005,0.001 ,0.002, 0.005 and 0.01 )C³/L , to remove the sticky substance of common carp (Cyprinus carpio L.) eggs, compared with the traditional method (fertilizing solution and 0.5 g tannine/L. water).The results indicated the possibility of using the extract at concentration (0.001 ,0.002,0.005 and 0.01) C³/L , without any adhesions with higher fertilizing and hatching rate in the concentration ( 0.005 and 0.01) C³/L than that of the traditional method which has no significant differences with the concentration( 0.001 and 0.002) C³/L. Also the result showed a short period of hatching in all the experimented concentration of Pineapple juice than the control treatment.